Mindful storytellers: Emerging pragmatics and theory of mind development - Fernandez, Camila (First language, 2013)
Emerging pragmatic language skills involve social, cognitive and linguistic abilities, including children’s awareness of the conversational partner’s mental states. The present study investigated the relation between children’s theory of mind (ToM) and features of pragmatic language skills assessed through narrative discourse. One hundred and fifteen Spanish-speaking children attending preschool and first grade (57 girls, 58 boys) participated. Children completed a standardized measure of receptive language, narrated a wordless picture book and completed first- and second-order ToM tasks. ToM was significantly related to various pragmatic language features. Hierarchical regression analyses showed that second-order ToM scores were a significant predictor of pragmatic language skills. Findings suggest that children’s communicative competence in social contexts, to some extent, requires the development of higher-order social-cognitive reasoning.